THE BENEFITS OF GAME THERAPY IN NEUROLOGICAL PHYSIOTHERAPEUTIC TREATMENT - Alves de Souza, Gabriel (Health and Society, 2023)
Game therapy is a technique that uses videogames as a physical therapy resource to promote physical and cognitive rehabilitation of patients with different clinical conditions. Game therapy was developed in 2006 in Canada and arrived in Brazil in 2007, being recognized by the Federal Council of Physiotherapy and Occupational Therapy (COFFITO) since 2015. It works through movement sensors that capture the patients’ gestures and transform them into actions in games, stimulating motor coordination, balance, cardiovascular conditioning, and brain activity. It is a complementary therapy that does not replace conventional forms of treatment, but contributes in a playful and fun way to the recovery of patients.